1998
DOI: 10.4269/ajtmh.1998.59.600
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with SPf66 and subsequent infection with homologous and heterologous Plasmodium falciparum parasites.

Abstract: Abstract. In an area of intense transmission, a malaria vaccine could reduce infection due to the parasite types represented in the vaccine, but have no detectable effect on the overall frequency of infection if it did not protect against infection with heterologous parasites. These studies were performed to determine whether immunization with SPf66 decreased infection with homologous parasites containing the 11 amino acid peptide from merozoite surface protein-1 (MSP-1) in SPf66, or increased infection due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, there is little experimental evidence to suggest that this would work for malaria. Trials with antigen combinations such as Spf66 and NYVAC-7 have given inconsistent or poor results (3,23,24,35,39), and in none of these experiments is there evidence that the combination performs better than single antigens. Shi et al (34) demonstrated the ability to raise growth-inhibitory sera in rabbits by immunization with multiple blood-stage epitopes but did not demonstrate that this approach was more effective than a particular epitope given singly.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little experimental evidence to suggest that this would work for malaria. Trials with antigen combinations such as Spf66 and NYVAC-7 have given inconsistent or poor results (3,23,24,35,39), and in none of these experiments is there evidence that the combination performs better than single antigens. Shi et al (34) demonstrated the ability to raise growth-inhibitory sera in rabbits by immunization with multiple blood-stage epitopes but did not demonstrate that this approach was more effective than a particular epitope given singly.…”
Section: Discussionmentioning
confidence: 99%
“…Filter paper blots were extracted as described previously [ 12 14 ]. After extraction and storage at 4 °C, parasite DNA was amplified using the polymerase chain reaction (PCR) with Taq polymerase and allotype-specific primers for the Block 2 region of msp1 [ 12 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The malaria vaccine SPf66 contains a 11‐mer peptide corresponding to part of the block 1 region of the polymorphic antigen MSP1. Study of parasites obtained from subjects immunized with this vaccine in The Gambia or in Kenya and from controls did not show any evidence for selection against parasites with the MSP1 block allele similar to that in the vaccine (Masinde et al . 1998; Haywood et al .…”
Section: Strain Specific Protection and Vaccinationmentioning
confidence: 99%